Effect of fullerene coating on silicon thin film anodes for lithium rechargeable batteries - Arie, Arenst Andreas; Chang, Wonyoung; Lee, Joong Kee (Journal of solid state electrochemistry, 2010)
To improve the electrochemical performances of Si thin film anodes for lithium rechargeable batteries, fullerene thin films are prepared by plasma-assisted evaporation methods to be used as coating materials. Analyses via Raman and X-ray photoelectron spectroscopy indicate that amorphous polymeric films originated from fullerene are formed on the surface of the silicon thin film. The electrochemical performance of these fullerene-coated silicon thin film as an anode material for rechargeable lithium batteries has been investigated by cyclic voltammetry, charge/discharge tests, and electrochemical impedance spectroscopy. The fullerene-coated Si thin films demonstrated a high specific capacity of above 3,000 mAh g −1 as well as good capacity retention for 40 cycles. In comparison with bare silicon anodes, the fullerene-coated silicon thin film showed superior and stable cycle performance which can be attributed to the fullerene coating layer which enhances the Li-ion kinetic property at the electrode/electrolyte interface.